2010
DOI: 10.3899/jrheum.091176
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Circulating CD28-negative T Cells in Patients with Rheumatoid Arthritis Treated with Abatacept Are Correlated with Clinical Response

Abstract: After therapy with abatacept, circulating CD28- T cells and other effector populations decrease in patients with RA. This decrease is correlated with clinical response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 31 publications
4
36
1
1
Order By: Relevance
“…Scarsi et al have shown changes in populations of CD28-expressing CD8 T cells in abatacept-treated rheumatoid arthritis (16) and that the baseline number of circulating CD28-negative T cells predicts remission (17). These and our findings may be related, but CD28 was not incorporated into our current panel, and future studies will be needed to examine whether these observations align.…”
Section: Discussionmentioning
confidence: 99%
“…Scarsi et al have shown changes in populations of CD28-expressing CD8 T cells in abatacept-treated rheumatoid arthritis (16) and that the baseline number of circulating CD28-negative T cells predicts remission (17). These and our findings may be related, but CD28 was not incorporated into our current panel, and future studies will be needed to examine whether these observations align.…”
Section: Discussionmentioning
confidence: 99%
“…However, Scarsi et al observed that the effect of anti-TNF-a treatment positively correlated with the clinical response [69]. The same group also showed that the baseline numbers of CD4 + CD28 -T cells in the blood of RA patients can predict the response to TNF-a inhibition [70].…”
Section: Viral Infectionsmentioning
confidence: 96%
“…Others demonstrated reduction of CD8+CD28- and late-stage CD8 effector memory, but not CD4+CD28- T-cells after 48 weeks of abatacept treatment. The decreases of CD28- cells among both CD4+ and CD8+ T lymphocyte populations after abatacept therapy were correlated with the clinical response as measured by DAS28/CRP [213]. Interestingly, the absolute numbers of CD28- T-cells (before treatment) were found to predict the response to abatacept [214].…”
Section: Effects Of Ra Treatment On the Aged Profile In Ramentioning
confidence: 99%